The influence of learning anxiety and involution on motivation among undergraduate English majors in Beijing and Macau - Sukjairungwattana, Paisan; Xu, Wei; Dong, De; Li, Fan (Frontiers in Education, 2025)
The aim of this study is to examine how learning anxiety and involution influence students’ learning motivation, the interrelationships among anxiety, involution, and the four language skills (listening, speaking, reading, and writing), as well as the potential variations in these relationships among English major students in different educational backgrounds, specifically in Beijing and Macau. This study employed quantitative research methods to collect data on learning anxiety, involution, and motivation levels from university students in both cities. The results indicate that both groups exhibited motivation levels higher than the average, moderate levels of anxiety and involution, and significant effects of anxiety and involution on motivation. Furthermore, interconnections were observed among the four language skills. Moreover, variations in the results were found across different cultural backgrounds. This study holds important theoretical significance in understanding the impact of affect and positive psychology on English learning, as well as exploring the differences in English learning within diverse cultural contexts.